Genetic influences on splenic function in coeliac disease. Issue 10 (October 1985) - O'Grady, J G; Stevens, F M; McCarthy, C F
Abstract : Splenic function was assessed using 'pitted' erythrocyte counts in 61 first degree relatives of patients with coeliac disease. 'Pitted' erythrocyte counts were normal in 12 parents, but were raised in 20% of 49 siblings and/or children of coeliac patients. First degree relatives had higher 'pitted' erythrocyte counts than normal controls (p = 0.002). The counts were lower in coeliac relatives than in age matched coeliacs (p = 0.0001), but no difference was present between the relatives and coeliac patients whose small bowel mucosa was morphologically normal. Considerable interfamily variation was found in 'pitted' erythrocyte counts, both in the coeliac patients and first degree relatives, and the pattern tended to 'run true' within families. The genetic factor influencing splenic function in coeliac disease is not HLA-linked but seems to be associated with a second, probably recessive, gene influencing the inheritance of coeliac disease.